PENGARUH KUALITAS PRODUK, KEPERCAYAAN, DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN DENGAN MINAT BELI SEBAGAI VARIABEL INTERVENING PADA TOKO JAKARTA FASHION SUPER MODEL DI SITUBONDO - M Imam Muzemmil; Riska Ayu Pramesthi; Ida Subaida (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
This study aims to analyze the influence of product quality, trust, and location on purchase decisions with buying interest as an intervening variable at Jakarta Fashion Super Model Store in Situbondo. The research method used is quantitative with a survey approach. The sampling technique applied is purposive sampling with 94 respondents. Data analysis was conducted using SmartPLS 3.0. The results show that product quality, trust, and location have a positive and significant effect on both buying interest and purchase decisions. Furthermore, buying interest significantly influences purchase decisions. The study also finds that buying interest significantly mediates the effect of product quality, trust, and location on purchase decisions. These findings highlight the importance of those factors in improving consumer purchasing decisions.